The Impact of Technology in Teaching and Learning English as Foreign Language : TESOL Context - Nur Amalia Solikhah (Journal Corner of Education, Linguistics, and Literature, 2023)
This paper is an effort to explore the impact of technology in the context of Teaching and Learning English to Students as their foreign languages. At first, it analyzes the background of the evolving field of technology in English language learning. Second, it delineates the growth of English through technology. Third, it explains the various necessities of technology in learning English. After that, it highlights the possible disadvantages of technology. Next, it explains the importance of striking a balance between technology and traditional teaching and learning. Finally, the researcher concludes that a judicious and balanced use of technology have a positive impact on learning English as a foreign language. Therefore, technology tools can clearly be effective in improving the students’ language and communication skills as the desired pedagogic outcome in the TESOL classroom.